Herbal - Synthetic Drug Interactions - Kintoko, Kintoko; Ananda, Aghnia Nabila; Ridho, Anisa Rifka; Makati, Annisa Camellia; Yanti, Asti Afrida; Wahyuni, Dina; Maghfirah, Yolanda Sajjida; Isnaini, Isnaini (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background:  Herbal medicine is currently one of the therapeutic options chosen by the community because it is considered relatively safer and has minimal side effects. Not only used as a single drug, but herbal ingredients can also be combined with synthetic drugs. However, using herbal and synthetic drugs simultaneously can cause a variety of interactions, including synergism, antagonism, and additive effects (potentiation).Objective: Therefore, it is crucial to do a literature study on the reaction of various herbal medicines to unwanted synthetic drugs to prevent the adverse effects that can be caused.Methods: The literature review is processed based on academic journals published on NCBI, PubMed, and online journal sources that discuss the interactions between herbal medicines and synthetic drugs from 1997 to 2022.Results: Herbal drug interactions can be avoided or managed by providing correct patient advice based on reliable information.Conclusion:The main basic principles of administering these medicines include the doctor's full awareness of the effects and interactions between herbal medicines and herbal medicines and herbal medicines with synthetic drugs.